Pengaruh Perlakuan Awal Terhadap Kecepatan Berkecambah - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
ABSTRACT The objective of this research is-to observe the effect of initial treatmen to the percent and velocity of germination. The initial treatment consisted of mechanical, physical and chemical treatment. Four mechanical treatment were scrapping off part of the microphyl